Maternal employment and childhood overweight in low- and middle-income countries - Oddo, Vanessa M (Public Health Nutr, 2017)
OBJECTIVE: To investigate the association between maternal employment and childhood overweight in low- and middle-income countries (LMIC). DESIGN/SETTING: We utilized cross-sectional data from forty-five Demographic and Health Surveys from 2010 to 2016 (n 268 763). Mothers were categorized as formally employed, informally employed or non-employed. We used country-specific logistic regression models to investigate the association between maternal employment and childhood overweight (BMI Z-score>2) and assessed heterogeneity in the association by maternal education with the inclusion of an interaction term. We used meta-analysis to pool the associations across countries. Sensitivity analyses included modelling BMI Z-score and normal weight (weight-for-age Z-score≥−2 to <2) as outcomes. SUBJECTS: Participants included children 0–5 years old and their mothers (aged 18–49 years). RESULTS: In most countries, neither formal nor informal employment was associated with childhood overweight. However, children of employed mothers, compared with children of non-employed mothers, had higher BMI Z-score and higher odds of normal weight. In countries where the association varied by education, children of formally employed women with high education, compared with children of non-employed women with high education, had higher odds of overweight (pooled OR=1·2; 95 % CI 1·0, 1·4). CONCLUSIONS: We find no clear association between employment and child overweight. However, maternal employment is associated with a modestly higher BMI Z-score and normal weight, suggesting that employment is currently associated with beneficial effects on children’s weight status in most LMIC.